The destruction of the universe in the perspective of Science and Islam - Ismayana, Winda (Maliki Interdisciplinary Journal, 2024)
In the Islamic religion there is the holy book Al-Qur'an which is a guide for mankind. Humans are perfect creatures that Allah has provided with reason to be able to understand the verses of the Al-Qur'an functionally. Besides that reason makes humans discover knowledge but can be balanced between spiritual and intellectual. There are several problems for humanity, one of which is about the destruction of the universe.